Inhibition of acid‐sensing ion channel currents by propofol in rat dorsal root ganglion neurons. (April 2014) - Lei, Zhen; Li, Xiaoyu; Wang, Guizhi; Fei, Jianchun; Meng, Tao; Zhang, Xinyu; Yu, Jingya; Yu, Jingui; Li, Jingxin
Summary Acid‐sensing ion channels (ASICs), part of the epithelial sodium channel/degenerin family, are activated by extracellular protons. The ASICs play a significant role in the acidosis‐mediated perception of pain. The anaesthetic agent propofol also exerts antinociceptive effects, but the underlying mechanisms for this effect are not clear. We used whole‐cell patch clamping to investigate the effect of propofol on proton‐gated currents in: (i) rat dorsal root ganglion (DRG) neurons; and (ii) HEK293 cells transfected with either ASIC1a or ASIC3. Propofol inhibited the amplitude of proton‐gated currents in DRG neurons, but did not change the sensitivity of ASICs to H+. Notably, propofol altered acid‐evoked excitability of rat DRG neurons and decreased the number of action potentials induced by acid stimuli. In addition, we demonstrated that propofol inhibited ASICs by directly binding with these channels in HEK293 cells. These results suggest that propofol inhibits proton‐gated currents in DRG neurons and that inhibition of proton‐gated currents explains, in part, the antinociceptive effects of propofol in primary afferent neurons.